(untitled) (World Bulletin of Management and Law, 2022)
Recently, organizations sensed great challenges facing them, represented by accelerating environmental changes, especially technological changes that were and still are the biggest drivers behind environmental dynamism that many business organizations could not keep pace with, because of their traditional business models and structures. Add to that the emergence of Corona pandemic, which threatened the global economy and stunted its growth, causing panic about its disastrous results, which are expected to continue for a longer period before recovering. The Corona epidemic has imposed an unfamiliar pattern on how organizations deal with their internal and external environments, as it has become necessary for them to search for non-traditional business models that are able to cope with emerging conditions.The current study comes to shed light on the concept of leadership agility and determine the competences that agile leader should possess in general, as well as diagnosing the levels of leadership agility of deans of faculties under study.